Adjectival Retention: Persuasive Texts Students Universitas Negeri Makassar - Azis, Azis; Juanda, Juanda; Korompot, Chairil Anwar (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
This research contributes to language development, especially adjectival retention as a very basic resilience in the text. Research on adjectives has been conducted by (Kennedy, 2013), (Schiff et al., 2014), (Sharma et al., 2015), (Sato et al., 2016), (Cutillas & Tolchinsky, 2017) Compared to the previous studies, however, the present study focuses on adjectival retention. In addition, the research findings also provide an understanding of the use of adjectives with the meaningfulness contained in the sentence. This research is a qualitative one, using a content analysis method. The data consist of persuasive essays written by 83 students of Indonesian Language and Literature Education Program in the Faculty of Languages and Literature at State University of Makassar, submitted during March to September 2019 period. While the research data were in the form of adjectives in the essays submitted, the research instrument was the researchers themselves. Data collection was done by giving assignments to the students to write persuasive essays. Data analysis techniques were identifying, reducing, presenting the data, verifying, and drawing conclusions about adjectival retention. The findings of the study indicate the following cases of adjectival retention: (a) weakening of positive adjectival retention; (b) intensive retention occurring not only with the precursor which precedes it, but also with the constituent following it; (c) elative retention appearing only after the use of verbs in the sentence; (d) excessive adjectival retention having a formation that occurs due to a conjunction stating the cause; (e) retention of argumentative adjectives placing emphasis on the part of the core sentence; (f) retention of attenuate adjectives reinforcing one another and not weakening the other parts. Overall, some 42% of the essays contain adjectival retention and 58% of them were without adjectival retention.